Five-Hour Detection of Intestinal Colonization with Extended-Spectrum-β-Lactamase-Producing Enterobacteriaceae Using the β-Lacta Phenotypic Test: the BLESSED Study - Salah Gallah; Maximilien Scherer; Thierry Collin; Camille Gomart; Nicolas Veziris; Yahia Benzerara; Marc Garnier (Microbiology Spectrum, 2023)
ABSTRACT Extended-spectrum-β-lactamase (ESBL)-producing Enterobacteriaceae (ESBL-PE) intestinal colonization is of particular concern as it negatively impacts morbidity and is the main source of external cross-contamination in hospitalized patients. Contact isolation strategies may be caught out due to the turnaround time needed by laboratories to report intestinal colonization, during which patients may be inappropriately isolated or not isolated. Here, we developed a protocol combining enrichment by a rapid selective subculture of rectal swab medium and realization of a β-Lacta test on the obtained bacterial pellet (named the BLESSED protocol). The performances of this protocol were validated in vitro on 12 ESBL-PE strains spiked into calibrated sample suspensions and confirmed in clinical settings using 155 rectal swabs, of which 23 (reference method) and 31 (postenrichment broth culture) came from ESBL-PE carriers. In vitro, the protocol detected, with 100% sensitivity, the presence of the 12 ESBL-PE strains from 104 CFU/mL. In the clinical validation cohort, 22 out of the 23 (reference method) and 28 out of the 31 (postenrichment broth culture) ESBL-PE-positive rectal samples were accurately detected. The diagnostic performances for ESBL-PE detection, considering all ESBL-PE carriers, were 90% sensitivity, 98% specificity, an 87% positive predictive value, and a 98% negative predictive value. Our protocol is a rapid and low-cost method that can detect intestinal colonization with ESBL-PE in less than 5 h more accurately than the reference method, opening the field for further studies assessing a rapid and targeted isolation strategy applied only to patients with a positive BLESSED protocol result. IMPORTANCE To both improve the efficiency of contact isolation among ESBL-PE carriers and avoid the unnecessary isolation of noncolonized patients, we should reduce the turnaround time of ESBL screening in laboratories and improve the sensitivity of diagnostic methods. The development of rapid and low-cost methods that satisfy these two goals is a promising approach. In this study, we developed such a technique and report its good diagnostic performance, opening the door for further studies assessing a rapid and targeted isolation strategy applied in a few hours only for patients truly colonized with ESBL-producing bacteria.